Law No. 9 of the year 2018 Amending Certain Provisions of Law No. 121 of the Year 1982 Concerning the Register of Importers = قانون رقم 9 لسنة 2018 بتعديل بعض أحكام قانون رقم 121 لسنة 1982 فى شأن سجل المستوردين - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic